Air-stable and reusable cobalt ion-doped titanium oxide catalyst for alkene hydrosilylation. Issue 16 (2nd August 2019) - Mitsudome, Takato; Fujita, Shu; Sheng, Min; Yamasaki, Jun; Kobayashi, Keita; Yoshida, Tomoko; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract : Air-stable and highly reusable cobalt ion-doped titanium oxide catalyst was developed for alkene hydrosilylation. Abstract : Alkene hydrosilylation is important for the synthesis of organosilicon compounds, for which precious metal complexes have been used as industrial catalysts. Considering environmental and economic concerns, the development of earth-abundant metal catalysts with high stability, easy separability, and high reusability is strongly desired. Herein, we report that a new cobalt ion-doped titanium dioxide (Co/TiO2 ) catalyst was synthesized by hydrogen treatment method. The Co/TiO2 catalyst acts as a highly efficient heterogeneous catalyst for the anti-Markovnikov hydrosilylation of alkenes under solvent-free conditions. Various alkenes were selectively converted to the corresponding alkylsilanes. This catalyst showed high stability in air and high reusability with maintained activity. The investigation of the relationship between the active site structure and catalytic performance of Co/TiO2 disclosed that the high stability and durability of Co/TiO2 are originated from the strong interaction between Co and TiO2 through the formation of CoTiO3 solid solution species.